Supraventricular Tachycardia in Children - Igor A. Kovalev; Igor A. Khamnagadaev; Lilia I. Svintsova; Tatiana K. Kruchina; Dinara I. Sadykova; Dina R. Sabirova; Zulfiya R. Khabibrakhmanova; Maria A. Shkolnikova (Педиатрическая фармакология)
Rhythm and conduction disorders of the heart occupy one of the leading places in the structure of cardiovascular pathology in children. Supraventricular tachycardias means tachyarrhythmias, caused by abnormal myocardial excitation with the source of rhythm localization above the His bundle bifurcation — in the atria, atrioventricular junction (node), and also arrhythmias with circulation of the excitation wave between the atria and the ventricles with additional atrial compounds. The team of authors presents clinical recommendations developed on the principles of evidence-based medicine, including all stages of diagnosis and treatment of children with supraventricular tachycardias. The use of recommendations in clinical practice allows to selecte the best strategy for diagnosis and treatment of supraventricular tachycardia in a particular patient.